Tasks before the twelfth congress of the Russian Communist Party - Trotski, Leon; Pearce, Brian (London : New Park publications, 1975)
Bibliotheek François Vercammen
Engels
Brochure
Keywords: Communistische Partij van de Sovjet-Unie.